Multicolor imaging of calcium-binding proteins in human kidney stones for elucidating the effects of proteins on crystal growth - Yutaro Tanaka (Nature Portfolio, 2021)
Abstract The pathogenesis of kidney stone formation includes multi-step processes involving complex interactions between mineral components and protein matrix. Calcium-binding proteins in kidney stones have great influences on the stone formation. The spatial distributions of these proteins in kidney stones are essential for evaluating the in vivo effects of proteins on the stone formation, although the actual distribution of these proteins is still unclear. We reveal micro-scale distributions of three different proteins, namely osteopontin (OPN), renal prothrombin fragment 1 (RPTF-1), and calgranulin A (Cal-A), in human kidney stones retaining original mineral phases and textures: calcium oxalate monohydrate (COM) and calcium oxalate dihydrate (COD). OPN and RPTF-1 were distributed inside of both COM and COD crystals, whereas Cal-A was distributed outside of crystals. OPN and RPTF-1 showed homogeneous distributions in COM crystals with mosaic texture, and periodically distributions parallel to specific crystal faces in COD crystals. The unique distributions of these proteins enable us to interpret the different in vivo effects of each protein on CaOx crystal growth based on their physico-chemical properties and the complex physical environment changes of each protein. This method will further allow us to elucidate in vivo effects of different proteins on kidney stone formation.